Acutely increased workload is correlated with significant injuries among national basketball association players - Orringer, M. J.; Pandya, N. K. (International Journal of Sports Science & Coaching, 2022)
Background Particularly at the level of professional athletics, injury prevention is of critical importance. We hypothesized that elevated in-game statistics over a period of 3-10 games places increased cumulative stress on players` joints and thus predisposes players to injury.